2014
DOI: 10.4310/cag.2014.v22.n1.a1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of spectral function of lower energy forms and Bergman kernel of semi-positive and big line bundles

Abstract: In this paper we study the asymptotic behaviour of the spectral function corresponding to the lower part of the spectrum of the Kodaira Laplacian on high tensor powers of a holomorphic line bundle. This implies a full asymptotic expansion of this function on the set where the curvature of the line bundle is non-degenerate. As application we obtain the Bergman kernel asymptotics for adjoint semi-positive line bundles over complete Kähler manifolds, on the set where the curvature is positive. We also prove the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 65 publications
0
62
0
Order By: Relevance
“…4.5], we proved that the stabilization graph of a semistable (pointed) graph G is strong if and only if G is strong. So the corollary follows from (32) and (33).…”
Section: Remark 33mentioning
confidence: 59%
“…4.5], we proved that the stabilization graph of a semistable (pointed) graph G is strong if and only if G is strong. So the corollary follows from (32) and (33).…”
Section: Remark 33mentioning
confidence: 59%
“…When M is complete and L is uniformly positive on M with √ −1R K * M and ∂Θ bounded below, where R K * M is the curvature of the bundle of (n, 0) forms, Ma-Marinescu [15] obtained the asymptotic expansion of the Bergman kernel for q = n − = 0. More generally, if M is any complex manifold and (q) k has O(k −n 0 ) small spectral gap on an open set D ⋐ M (see Definition 1.5 in [9], for the precise meaning of O(k −n 0 ) small spectral gap), then it is known by a recent result (see Theorem 1.6 in [9]) that the Bergman kernel admits a full asymptotic expansion in k on D. The coefficients of these expansions turned out to be deeply related to various problem in complex geometry (see e.g. [3], [4], [5]).…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…We write [9], for the precise meaning of O(k −n 0 ) small spectral gap). From this observation and Theorem 4.12, Theorem 4.14 in [9], we deduce the following…”
Section: The Asymptotic Expansion Of the Bergman Kernelmentioning
confidence: 99%
“…Let P k,M \Σ be the associated Bergman projection on M \ Σ and let P k,M \Σ (x) be the associated Bergman kernel function. In [8], we showed that…”
Section: Theorem 32 With the Notations And Assumptions Used Beforementioning
confidence: 99%
“…In this paper, we survey recent results in [8] about the asymptotic expansion of Bergman kernel and we give a Bergman kernel proof of Kodaira embedding theorem. …”
mentioning
confidence: 99%